2019
DOI: 10.21203/rs.2.17174/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of Multidisciplinary Intervention Model in Nursing of Older patients with Diabetes

Abstract: Objective To evaluate the application of multidisciplinary treatment (MDT) model in nursing of elderly patients with diabetes.Methods A total of 166 elderly diabetic patients were retrospectively selected. They were randomly and equally divided into the MDT group and the control group. The patients in the control group were treated with the traditional nursing method. And the patients in the MDT group were treated with a multidisciplinary team. The hospitalization time, hospital costs, incidence of diabetes-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Three papers (Boter, 2004; Burton & Gibbon, 2005; Ostwald et al, 2013) did not explain the method of random sequence generation in detail, two papers (Deyhoul et al, 2020; Mei et al, 2017) did not specify how to implement allocation hiding and three papers (Forster & Young, 1996; Johnston et al, 2009; Tielemans et al, 2015) did not describe these two parts in detail, which indicated the possibility of selection bias in these studies. Fourteen papers (Boter, 2004; Burton & Gibbon, 2005; Deng et al, 2020; Deyhoul et al, 2020; Eames et al, 2013; Forster & Young, 1996; Johnston et al, 2009; Lin et al, 2022; Mei et al, 2017; Minshall et al, 2020; Ostwald et al, 2013; Tielemans et al, 2015; Wang et al, 2015; Zhao, 2021) did not blind the study subjects and/or the intervention provider and had a high risk of implementation bias. One paper (Clark et al, 2003) did not mention whether the study subjects or intervention providers were blinded, indicating possible implementation bias.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three papers (Boter, 2004; Burton & Gibbon, 2005; Ostwald et al, 2013) did not explain the method of random sequence generation in detail, two papers (Deyhoul et al, 2020; Mei et al, 2017) did not specify how to implement allocation hiding and three papers (Forster & Young, 1996; Johnston et al, 2009; Tielemans et al, 2015) did not describe these two parts in detail, which indicated the possibility of selection bias in these studies. Fourteen papers (Boter, 2004; Burton & Gibbon, 2005; Deng et al, 2020; Deyhoul et al, 2020; Eames et al, 2013; Forster & Young, 1996; Johnston et al, 2009; Lin et al, 2022; Mei et al, 2017; Minshall et al, 2020; Ostwald et al, 2013; Tielemans et al, 2015; Wang et al, 2015; Zhao, 2021) did not blind the study subjects and/or the intervention provider and had a high risk of implementation bias. One paper (Clark et al, 2003) did not mention whether the study subjects or intervention providers were blinded, indicating possible implementation bias.…”
Section: Resultsmentioning
confidence: 99%
“…One paper (Deyhoul et al, 2020) did not use assessments of outcome measures that were done by blinded raters, which implied a risk of measurement bias. Three papers (Clark et al, 2003; Zhao, 2021) did not account for the loss to follow‐up, and their outcome data were incomplete. Seven papers (Boter, 2004; Burton & Gibbon, 2005; Clark et al, 2003; Deyhoul et al, 2020; Forster & Young, 1996; Johnston et al, 2009; Ostwald et al, 2013) did not provide relevant information about the study protocol, suggesting that there may have been selective reporting of findings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations